New persistent opioid use among adolescents and young adults with sarcoma - Beauchemin, Melissa P.; Raghunathan, Rohit R.; Accordino, Melissa K.; Cogan, Jacob C.; Kahn, Justine M.; Wright, Jason D.; Hershman, Dawn L. (Cancer, 2022)
Background Adolescents and young adults (AYA) with sarcoma experience both acute and chronic pain related to their disease and treatment. Studies in older adults have reported a high risk of persistent opioid use after cancer therapy among previously opioid‐naive patients; however, few studies have evaluated posttreatment opioid use among AYAs. This article describes patterns of new persistent opioid use among AYAs in the year after treatment for sarcoma. Methods Opioid‐naive patients who were 10 to 26 years old and diagnosed with sarcoma (2008‐2016) were identified with the IBM Marketscan Database. Included subjects had an International Classification of Diseases code for sarcoma (ninth or tenth revision), received anticancer therapy (chemotherapy, surgery, and/or radiation) within 30 days of the first diagnosis code, and had continuous insurance coverage (commercial or Medicaid) for more than 12 months both before the diagnosis and after the last therapy. The primary outcome was new persistent opioid use, which was defined as at least 2 opioid prescriptions in the 12 months following treatment completion. Covariates included age, sex, insurance, tumor type, surgical procedure, mental health (MH) or substance use diagnoses before or during therapy, and concomitant lorazepam use. Results In total, 938 patients met the inclusion criteria; 521 (56%) were male, and 578 (62%) were younger than 18 years. In total, 727 (78%) had commercial insurance, and 273 (29%) had an MH diagnosis either before or during the treatment period. Of the total group, 464 (49%) used opioids during treatment only. Of those who used opioids during treatment, 135 (23%) received at least 2 prescriptions in the year after therapy. In a multivariable analysis, Medicaid versus commercial insurance (odds ratio [OR], 1.74; 95% confidence interval [CI], 1.15‐2.64) and non–soft tissue sarcoma (OR for Ewing sarcoma, 3.23; 95% CI, 1.81‐5.78; OR for osteosarcoma, 2.05; 95% CI, 1.36‐3.09) conferred a higher likelihood of new persistent use. Conclusions In this cohort of AYAs treated for sarcoma, 64% of the patients received opioid prescriptions during treatment, and 23% of these patients became new persistent users. Because of the risks associated with persistent opioid use, studies of novel pain management strategies along with age‐appropriate education and anticipatory guidance are urgently needed. Lay Summary Using an insurance claims database, we conducted a study to determine the rate of new persistent opioid use among adolescents and young adults treated for sarcoma. We found that 64% of adolescents and young adults treated for sarcoma received opioid prescriptions during treatment, and 23% of these patients met the criteria for new persistent opioid use. These findings support the need for age‐appropriate education and novel pain management strategies in this vulnerable population. In this cohort of adolescents and young adults treated for sarcoma, 64% of the patients received opioid prescriptions during treatment, and 23% of these patients became new persistent users. Because of the risks associated with persistent opioid use, studies of novel pain management strategies along with age‐appropriate education and anticipatory guidance are urgently needed.